Distribution and behaviour of nitrogen compounds in the surface water of Sungai Terengganu Estuary, Southern Waters of South China Sea, Malaysia - Suhaimi Suratman; Azyyati Abdul Aziz; Norhayati Mohd Tahir; Lee, Hin Lee (Penerbit Universiti Kebangsaan Malaysia, 2018)
A study was carried out to determine the distribution and behaviour of nitrogen (N) compounds (nitrite, nitrate, ammonia, dissolved and particulate organic nitrogen) in Sungai Terengganu estuary (TRE). Surface water samples were collected during ebb neap and spring tides for the longitudinal survey along the salinity gradient. The results indicated that all N compounds behave non-conservatively with addition during both tidal cycles, except for nitrate which exhibited removal behaviour during spring tide. In general, higher concentration of N compounds was observed during spring tide compared to neap tide. It is suggested that during spring tide, stronger water turbulence resulted in resuspension of nutrients in bottom sediment and lead to the increase in N compounds concentrations in the surface water. The diurnal survey for the freshwater station showed that the concentrations of N compounds follow the ebb and flood variations, whereas for the coastal station the reverse trend was observed. Comparisons with a previous study under similar tidal conditions show there was an increase in nitrite and ammonia concentrations in TRE, which was probably due to increase in discharge from the rapid development activities around this area. In addition, the presence of a breakwater at the lower part of the estuary may also contribute to the high nutrient content in the estuary due to restricted outflow of nutrients to the coastal area. Overall, the results from this study highlighted the importance of monitoring the N compounds for future protection of the estuary.